Manuelito - Amado, Elisa (Annick Press, 2019)
Manuelito's world in Guatamala's Maya highlands falls apart as his high school closes down indefinitely and the streets are filled with gangs, soldiers, and gunshots. Desperate to save their son and give him a new life, Manuelito's parents decide to send him on a dangerous journey through Mexico to the United States to live with his aunt--but of course the journey does not go as planned.